2021
DOI: 10.54433/jdiis.2021100004
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Usage of Instagram for Business and its Effect on Financial Performance and Non-Financial Performance

Abstract: The objective of this article is to study the factors which affect the Small and Medium Enterprises (SMEs) instagram use for business and its subsequent impact on financial and non-financial performance. The primary purpose of this study is to examine the effect of competency, cost-effectiveness, innovative behavior, and interactivity on instagram use for business, and consequences on firms' performance. Statistical analysis was performed on the data acquired through a survey questionnaire from 352 Malaysian S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 58 publications
2
16
1
Order By: Relevance
“…The literature review about s-commerce adoption by Salvatori and Marcantoni (2015) shows that businesses implement SMT mostly through enhanced internal and external communication; potential marketing and selling opportunities; strong consumer influence by known people; more trust, social presence, and intention to purchase; economic growth of the existing s-commerce; a decrease of initial fixed costs; easy product updates through social media; better prediction of market trends; improved accessibility of the network shops; and more accuracy of the referral system. Akbar (2021) finds that competency, cost-effectiveness, innovative behavior, and interactivity positively influence Instagram adoption by small to medium-sized enterprises.…”
Section: Organizational Contextmentioning
confidence: 96%
See 1 more Smart Citation
“…The literature review about s-commerce adoption by Salvatori and Marcantoni (2015) shows that businesses implement SMT mostly through enhanced internal and external communication; potential marketing and selling opportunities; strong consumer influence by known people; more trust, social presence, and intention to purchase; economic growth of the existing s-commerce; a decrease of initial fixed costs; easy product updates through social media; better prediction of market trends; improved accessibility of the network shops; and more accuracy of the referral system. Akbar (2021) finds that competency, cost-effectiveness, innovative behavior, and interactivity positively influence Instagram adoption by small to medium-sized enterprises.…”
Section: Organizational Contextmentioning
confidence: 96%
“…This is obvious as participants are young entrepreneurs who lack business skills and competencies to manage their microbusinesses (such as management and marketing). Akbar (2021) has found that competency positively influences Instagram adoption in small to medium-sized enterprises. Furthermore, Mack, Marie-Pierre, and Redican (2017) found that businesses struggle to derive value from Facebook for s-commerce purposes as they experience difficulties converting online interactions (likes and comments) into sales and effectively using SMT to increase brand awareness and profits.…”
Section: Identification Of Factors That Drive S-commerce Success For ...mentioning
confidence: 99%
“…AVE should be more than 0.50 for each item in the construct. It environmental management system with a value of less than 0.50 should be deleted to improve data quality (Hair et al, 2014;Akbar, 2021). An extracted value of 0.50 means that the construct explains half of the variance for the indicators, thus achieving convergence (Hair et al, 2013(Hair et al, , 2017.…”
Section: Analysis Construct Reliability and Validitymentioning
confidence: 99%
“…The photo-sharing and videosharing features on Instagram are designed to make interactions between business owners and consumers easier, more convenient, and more interesting (Soelaiman & Utami, 2021). As a marketing communication tool, Instagram is becoming an effective and low-cost social media trend for SMEs (Akbar, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of the use of social media applications is related to a business's financial or non-financial performance (Akbar, 2020). Improved performance through social media use can reduce transaction and coordination costs, resulting in closer relationships with customers and business partners.…”
Section: Introductionmentioning
confidence: 99%